Algorithms for Routing Optimization in Multipoint to Multipoint 4PL System. (9th June 2015) - Li, Jia; Liu, Yanqiu; Zhang, Ying; Xu, Shida
Abstract : Fourth party logistics (4PL) has been receiving great attention and studied by researchers. This paper studies multipoint to multipoint 4PL system routing optimization with reliability constraints. Objective factors which cause disturbances of transportation time are taken into consideration. The mathematical model of the multipoint to multipoint multitask routing optimization in 4PL system with reliability constraints is set up. To solve the model, a Messy Genetic Algorithm (Messy GA) with double arrays encoding method is designed. The experimental result is compared with the Enumeration Algorithm (EA), and it shows that this algorithm can find the satisfactory solution and is a powerful optimization method for solving the problem.